2021
DOI: 10.3892/ijmm.2021.5064
|View full text |Cite
|
Sign up to set email alerts
|

Epitranscriptomics of cardiovascular diseases (Review)

Abstract: RNA modifications have recently become the focus of attention due to their extensive regulatory effects in a vast array of cellular networks and signaling pathways. Just as epigenetics is responsible for the imprinting of environmental conditions on a genetic level, epitranscriptomics follows the same principle at the RNA level, but in a more dynamic and sensitive manner. Nevertheless, its impact in the field of cardiovascular disease (CVD) remains largely unexplored. CVD and its associated pathologies remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 288 publications
(382 reference statements)
0
7
0
Order By: Relevance
“…8,36 Under physiological and pathological conditions, episodic transcriptome alterations of noncoding RNAs are highly prevalent. 37 There are 2 types of noncoding RNAs: miRNAs (<50 nucleotides in length) and lncRNAs (>200 nucleotides in length). lncRNAs regulate gene expression in a more complicated manner and are more stable in cells than other RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…8,36 Under physiological and pathological conditions, episodic transcriptome alterations of noncoding RNAs are highly prevalent. 37 There are 2 types of noncoding RNAs: miRNAs (<50 nucleotides in length) and lncRNAs (>200 nucleotides in length). lncRNAs regulate gene expression in a more complicated manner and are more stable in cells than other RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery in 2006, the PLN-R14del mutation has been attracting an ever increasing research interest worldwide and PLN shown to contribute at varying degrees to disease pathology, while a number of other levels of molecular complexity, such as micro-RNAs, epigenetics and epitranscriptomics, remain to be explored (96)(97)(98)(99). While some of the experimental findings may appear conflicting at times, the intense, complementary efforts of the international PLN scientific community ensure continued progress with encouraging prospects towards the identification of promising therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…In the human heart, m6A patterns have been associated with cardiovascular remodeling, cardiac hypertrophy, ischemic heart disease, and heart failure. 72,73 Some recent data show that CVD risk factors can modify m6A, including in easy-to-collect biospecimens such as blood RNA. For instance, Kupsco et al showed in a study in Beijing, China, that the total levels of blood m 6 A were decreased in long-term smokers compared with nonsmokers.…”
Section: Gut Bacterial Epigenomics and Cardiovascular Diseasesmentioning
confidence: 99%